(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this manuscript, an approximate periodic solution of a nonlinear Jerk equation concerning the third order time derivative (ODE) is demonstrated. This method succeeds highly in constructing a periodic solution for Jerk nonlinear differential equations. The results investigated from this method are compared with those determined from other analytical and numerical methods. Our results demonstrate a significant consistency with the numerical solution in addition to the analytical methods.